Strategi dan Implementasi Net Zero Emission di Indonesia: Penyediaan Tenaga Listrik Terbarukan dalam RUPTL - Naylin Putri Harsa; Raisa Qolbina Ibrizzahra; Faradilla Kurnia Asyifa; Tabhita Prima Isnaeni (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
The global climate crisis, characterized by rising global temperatures due to greenhouse gas emissions, has prompted various countries, including Indonesia, to adopt Net Zero Emission (NZE) strategies to achieve a balance between emissions and carbon absorption by 2060 at the latest. This study aims to analyze the effectiveness of the implementation of the 2025–2034 Electricity Supply Business Plan (RUPTL) in achieving NZE targets, as well as to evaluate the role of the private sector, particularly Independent Power Producers (IPP), in renewable energy development. The research method used is a qualitative study with a descriptive-analytical approach to policy documents, secondary data, and relevant regulations. The results of the study indicate that although the RUPTL targets an additional 70% of electricity generation capacity from renewable energy, its implementation faces challenges such as coal dominance, regulatory uncertainty, and infrastructure limitations. The role of IPPs is considered strategic in financing and operating clean energy projects, but they are still constrained by bureaucracy, tariff schemes, and access to green financing. Therefore, policy synergy, regulatory reform, and fiscal incentives are needed to accelerate a fair and sustainable national energy transition.